Thyroid hormone therapy and procurement of livers from brain-dead donors - Novitzky, Dimitri; Mi, Zhibao; Videla, Luis A.; Collins, Joseph F.; Cooper, David K. C. (Endocrine research, 2016)
Hormonal therapy to brain-dead potential organ donors remains controversial. A retrospective study was carried out of hormonal therapy on procurement of organs in 63,593 donors in whom information on T 3 /T 4 therapy was available. In 40,124 donors, T 3 /T 4 and all other hormonal therapy was recorded. The percentages of all organs procured, except livers, were greater in T 3 /T 4 -treated donors. Nevertheless, if T 3 /T 4 therapy had been administered to the donor, liver transplantation was associated with significantly increased graft and recipient survival at 1 month and 12 months. The potential reasons for the lack of effect of T 3 /T 4 therapy on the number of livers procured are discussed.